Pengaruh Penerapan Model Problem Based Learning (PBL) Terhadap Pemahaman Konsep Matematis Siswa Kelas XI F3 SMA Negeri 4 Sijunjung - Jenius, Hendrik; Suryani, Mulia; Aima, Zulfitri (Polinomial : Jurnal Pendidikan Matematika, 2025)
This research is motivated by the lack of understanding of students' mathematical concepts and during the learning process, students are not yet active in learning mathematics. This study aims to determine whether there is an effect of the application of the Problem Based Learning (PBL) model on the understanding of mathematical concepts of class XI F3 students of SMA Negeri 4 Sijunjung. This type of research is experimental research. The design used in this study is the Pre-Experiment design with the concept used in this study is one group posttest only design. The study population was class XI F3 students of SMA Negeri 4 Sijunjung in the 2024/2025 academic year consisting of 3 classes. The sampling technique was carried out by Purposive Sampling. The instrument used in this study was a post-test in the form of an essay. The test statistics used for hypothesis testing are the one Sample T-Test.The results of the hypothesis test obtained t_count = 0.892 while t_table = 2.052 because t_count <t_table then accept H_0 with a real level of 0.05 meaning that the hypothesis is rejected. So it can be concluded that there is no influence of the application of the Problem Based Learning (PBL) model on the understanding of mathematical concepts of class XI F3 students of SMA Negeri 4 Sijunjung.